TINJAUAN RUPA DASAR SAMPUL BUKU “BIJAK BERBAHASA INDONESIA TEORI DAN APLIKASI” - Lejar Daniartana Hukubun (AKSA: Jurnal Desain Komunikasi Visual, 2023)
Basic art is a science that is used to train the basics of art and design. All the needs of art, regardless of whether it is in the form of painting, interior design, dance, design, etc., must have something to do with this knowledge. This journal attempts to discuss the cover of the book "Bijak Bahasa Indonesia Teori and Aplikasi" by Rishe Purnama Dewi, et al. This cavern has a basic visual arrangement that we can see, there is a repetition arrangement, the use of red hot colors, purple secondary colors and color binding colors. All of these are related and connected to one another, complemented by Sans Serif typography, with sizes, colors and layouts that are harmonious with each other, so that the cover design of this book is created.